Statutory tax burden and its avoidance in transitional Russia - Vlad Ivanenko (The University of Western Ontario, Department of Economics, 2002)
Was taxation so heavy in the Russian transition that firms could not stay afloat? is the question that this paper aims to answer. It details the fiscal structure and uses data from a number of sources to calculate statutory tax rates faced by businesses in 1995. The results show that statutory rates were manageable in the short run but unsustainable for several sectors in the long run. Important exceptions are the sectors of oil and gas extraction, which were overtaxed by statutory rates. The problem of tax avoidance and arrears is explored by looking on the difference between statutory and effective tax rates and effective and actual tax payments. Regression analysis shows that tax avoidance rises with gross profit suggesting that profitable firms lobby successfully for tax exemptions. However, when the sectors of gas and oil extraction are excluded from the regression, its estimate becomes insignificant. The paper conjectures that the government deliberately imposed unsustainable statutory tax rates since their consequent renegotiation with oil and gas producers was expected. Tax arrears are found to be strongly and positively correlated with the sectoral average employment. Yet, the hypothesis of strategic labor hoarding is rejected on the grounds that large tax debtors are large trade creditors as well. Finally, the paper asks the question of inflationary taxation. We recalculate input costs at their replacement values and find that almost all sectors are better off going out of business. Searching for possible explanations of why they continued to operate, the benefits and costs of receiving and extending trade and tax non-payments are considered. The results show that enterprises used non-payments to compensate incompletely for the costs of inflation.
Keywords: H3; P2; 330; Russian Transition; Statutory Taxation; Inflation